Sebuah Kajian Literatur Tentang Pengalaman Pasien Kanker Dalam Menghadapi Pandemi Covid-19: A Literature Review on the Experience of Cancer Patients in Facing the Covid-19 Pandemic - Made Satya Nugraha Gautama; Surya Wahyuni; Muflihul Huda; Istiqomah Nur Khasanah; Ulfa Hikmawati; Slamet Aminanto; Stefany Putri Sahureka; Orin Juliastuty Terawati Rizal (Fakultas Keperawatan Universitas Andalas, 2023)
The COVID-19 pandemic has caused various problems for cancer patients. Complaints related to changes in the medication process to the high risk of contracting COVID-19. This qualitative literature study aims to find out what the experiences of cancer patients are like during the COVID-19 pandemic. Articles were searched through Sciencedirect, Sage, Pubmed, and Scopus databases. Keywords using the PCC approach (Population (or participants)/Concept/Context) namely population